Analysis of the Legitimacy of PPPK Recruitment Implementation in Makassar City in 2024 - Amin, Nur Ichsan; Roslianah (Jurnal Pallangga Praja (JPP), 2025)
The announcement of the 2024 PPPK Phase I selection has been announced and can be declared a decision that meets the legal requirements, as announced simultaneously in December 2024 . The purpose of this study is to explain information that produces legitimate decisions, because it already has the requirements for legitimacy according to the provisions of applicable laws and regulations, and it turns out that the level of legitimacy is questionable, which in this study identified a lot of commotion that occurred after the announcement. It is a legitimacy crisis, it does not mean canceling the results of the decision or illegitimate, but it is a characteristic that shows the lack of credibility of a decision issued by the authorities, that the implementation of the first stage of the PPPK selection in 2024 has been carried out properly with the completeness of the requirements that have been set and regulated according to the same provisions for all selection participants based on their respective levels/levels of education and formation, so it is reasonable to call it a legal and rational decision, although it has been declared to have legality and has provided relief for those who have passed, but in terms of ethical legitimacy and sociological legitimacy, of course, there are still problems because it can be linked to a sense of justice and assessment of moral principles that are still being questioned by many parties, especially the dissatisfaction of those who have been declared to have failed or a number of observers for various reasons.